Just what you need: Simplifying electronic devices - Hodges, Steve; Harper, Richard (Microsoft Research, 2005)
Electronic consumer devices are becoming increasingly sophisticated. As a consequence, there is a real danger that they become harder and harder to use. One solution to maintaining ease of use is to limit the functionality exposed – less is often more in this regard. However, designers find this hard to do because of market demands; a wider range of features will potentially appeal to a wider audience. This paper outlines how a new approach to configuration may be the solution to this dilemma – whilst a device can support a large number of features, only a subset of these are exposed to the user, thereby keeping the usage model simple and easy to understand.
International Forum 'Less is more - Simple Computing in an Age of Complexity'.